“We don’t want it changed, do we?” - Gender and Sexuality in Role Playing Games - Schröder, Arne (Eludamos: Journal for Computer Game Culture, 2008)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:SimSun; panose-1:2 1 6 0 3 1 1 1 1 1; mso-font-alt:宋体; mso-font-charset:134; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:1 135135232 16 0 262144 0;} @font-face {font-family:"\@SimSun"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:134; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:1 135135232 16 0 262144 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Arial; mso-fareast-font-family:SimSun; mso-bidi-font-family:"Times New Roman"; mso-fareast-language:ZH-CN;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Video games in virtual worlds serve as reference points in negotiations of socially efficacious meanings. Therefore they entail the potential either to reproduce and affirm or to challenge traditional concepts of identity. This article presents findings of an in-depth content analysis of three role playing games with a male avatar belonging to the Gothic-series that was published between 2001 and 2006. Focal points of the examination were issues of gender and sexuality, how they are incorporated in narrative, interactions and rules of the game series, and how they are being discussed on fan sites and player forums.